Die vermeintlich pergamenische Importkeramik in Ephesos : Studien zur Typologie, Provenienz und Herstellungstechnik von so genannter Weißgrundiger Ware, Applikenkeramik und Pergamenischer Sigillata - Lätzer-Lasar, Asuman, (Archaeopress Archaeology, 2020)
This text presents comparative studies of three ceramic ware groups found at Ephesos (modern day Turkey): Appliqué Ware, White-grounded ware and Pergamene Sigillata. Until now they were considered to be products made in and imported from Pergamon, but intensive archaeometrical analysis demonstrate that they were produced locally.